PEMBUATAN ALAT PENGERING GULA SEMUT DENGAN KAPASITAS MAKSIMUM 120 KG MENGGUNAKAN BAHAN BAKAR GAS LPG - , TONY SATRIA PRAYOGA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Sugar are drying production process that can increase the durability of the product is sugar ants. For the drying process of sugar ants, usually waged naturally with the help of sunlight. With the drier sugar ants, the production process will not take long. The final task of designing tool dryer automated sugar ants are controlled by temperature controller. The air conditioning system uses the heat generated from the box that was burned by the stove and then exhaled by the blower. Using electrical controls as drier sugar ants can save fuel LPG, which can be proved with the functioning of the mechanism of opening and closing the valve on the solenoid valve and the spark jumps on electric lighters that have been integrated with a temperature controller. Testing without load, heating drying cabinet until the temperature reaches level 60 0C takes Â± 40 minutes and test with a maximum load of 120 kg of sugar ants during the drying process requires Â± 8 hours, with fuel consumption of 1.3 kg were used spent LPG gas from initial weight of 8 kg.